PROFIL PEDAGANG KAKI LIMA DAN EVALUASI KEBIJAKAN PUBLIK DALAM PENATAAN PEDAGANG KAKI LIMA - Indah Yuliasari (Universitas Indraprasta PGRI, 2016)
This study aimed to determine the profile Street Vendors at the location specified by the City, as well as the wishes of the people of the existence of street vendors. By studying the behavior of Street Vendors then be recognizable traits and stuff so it can be made the planning and arrangement in accordance with the Street Vendor Profile so that the evaluation of public policies that can be implemented.There is a need for Street Vendors by society makes the existence of street vendors even more and more. Surabaya City Government through the Regional Regulation No. 17 of 2003 on Structuring Traders Five feet have attempted to organize street vendors, among others, the determination of the location of the street vendors, but still not effective. Which is marked with the number of offenses committed by street vendors. From the location specified by the government of Surabaya, Surabaya Bungkul Park area is the perfect location as the location of street vendors because people are still high levels of traffic and a location that is in demand by the public and street vendors. Keywords: Street Vendor Profile, Evaluation of Public Policy